2023
DOI: 10.1097/jnn.0000000000000688
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in Patients With Moderate to Severe Acquired Brain Injury: Prevalence During 4 Weeks of Subacute Rehabilitation

Abstract: BACKGROUND: Malnutrition is associated with high rates of complication, longer hospital stays, and increased morbidity and mortality. Malnutrition defined as undernutrition is common in patients with acquired brain injury (ABI); however, estimates vary remarkably. This study aimed to describe malnutrition at admission and after 4 weeks of subacute inpatient neurorehabilitation in patients with ABI using the new global consensus definition of malnutrition. METHODS: One hundred thirty-three patients with moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…[2][3][4][5] At admission, nearly half of patients fulfil the Global Leadership Initiative on Malnutrition (GLIM) criteria 6 7 and 10% remain undernourished after 4 weeks of rehabilitation. 8 Upon referral to in-hospital rehabilitation, a majority of patients with ABI experience weight loss relative to their weight at admission. Long-term undernutrition is known to persist in about one-third of community-dwelling patients with ABI.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] At admission, nearly half of patients fulfil the Global Leadership Initiative on Malnutrition (GLIM) criteria 6 7 and 10% remain undernourished after 4 weeks of rehabilitation. 8 Upon referral to in-hospital rehabilitation, a majority of patients with ABI experience weight loss relative to their weight at admission. Long-term undernutrition is known to persist in about one-third of community-dwelling patients with ABI.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, few recent reports concerning patients with moderate to severe acquired brain injuries have indicated that malnutrition was common at admission to the intensive rehabilitation unit (IRU) after hospitalization in the intensive care unit (ICU) [11,12]. Thus, an early assessment of nutritional risk is crucial to carry out the needed therapies and to prevent the consequences.…”
Section: Introductionmentioning
confidence: 99%